Persepsi Guru Terhadap Penerapan Sistem Full Day School: Studi Kasus di SMAN 1 Citeureup - Anggraeni, Novi; Rohman, Baeti; Sholichah, Aas Siti (Fakultas Tarbiyah dan Ilmu Tarbiyah, Universitas PTIQ Jakarta, 2020)
This paper discusses the teacher's perception of the application of the full day school system atSMAN 1 Citeureup. This research is motivated by the existence of an innovation in educationset by the government about the school day that is full day school. This type of research is adescriptive qualitative research with field research approach. The research data collectiontechniques using observation, interviews and documentation. The results of this study indicate that (1) Some teachers respond positively to the full day school policy, if the school is able tosupport all aspects needed by both teachers and students, starting from the concept of managinga full day school learning that is well planned, structured and directed so that it is more effectivein carrying out the learning process and the development of adequate facilities andinfrastructure (2) teachers' perceptions about the advantages of full day school systems can bea solution for parents who care about the moral crisis that is being experienced by students atthis time. Furthermore, as a means of improving the quality of student morals for the better,and to maximize student time to be more useful by developing students 'talents, interests andcreativity (3) teachers' perceptions of the weaknesses of full day school lies in the technicalimplementation in schools, the lack of student socialization with the surrounding environmentinadequate places of residence and facilities and infrastructure (4) management of full dayschool learning in SMAN 1 Citeureup in accordance with PP No. 19 of 2005 concerningNational Education Standards which include program planning, implementation andevaluation.